2020
DOI: 10.1111/1756-185x.13931
|View full text |Cite
|
Sign up to set email alerts
|

Weekly split‐dose regimen for oral methotrexate reduced polyglutamation in red blood cells in patients with rheumatoid arthritis compared with single‐dose regimen: Results from a multicentered randomized control trial

Abstract: Methotrexate (MTX) is a globally recognized disease-modifying anti-rheumatic drug considered as the anchor drug for the treatment of rheumatoid arthritis (RA); however, the major dose regimens vary among countries and region. 1-3 For example, the weekly dose is taken as a single dose in the US, but is generally divided into 2-4 parts taken at 12-hour intervals in Japan when it exceeds 8 mg. The Japanese guidelines for the use of MTX recommend the division of weekly doses above 8 mg to reduce gastrointestinal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…32 Additionally, previous studies have reported the high incidence of medication error associated with the weekly dose of MTX. 14,20,21 Despite there are a few studies that modify the standard dosing method of MTX, [19][20][21]33 the current one evaluates daily administration of a low dose of MTX compared to an identical weekly dosage. Pandya et al found that in patients under weekly dosage scheme, remission was achieved after 4 weeks on treatment, with a decrease of the basal swollen joint count of (mean AE SD) 6.6 AE 6.6 to 4.10 AE 6.14; however, this response was not sustained in the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…32 Additionally, previous studies have reported the high incidence of medication error associated with the weekly dose of MTX. 14,20,21 Despite there are a few studies that modify the standard dosing method of MTX, [19][20][21]33 the current one evaluates daily administration of a low dose of MTX compared to an identical weekly dosage. Pandya et al found that in patients under weekly dosage scheme, remission was achieved after 4 weeks on treatment, with a decrease of the basal swollen joint count of (mean AE SD) 6.6 AE 6.6 to 4.10 AE 6.14; however, this response was not sustained in the follow-up.…”
Section: Discussionmentioning
confidence: 99%